The Effect of Auditor's Competence, Task Complexity and Digital Forensic Support on Auditor's Ability in Detecting Fraud - Andy Mahbub Arif Widiyanto (Budapest International Research and Critics University, 2022)
Technological developments affect fraud detection. Perpetrators hide traces of crime using activities in digital form. Digital forensic skills have become a new necessity. However, the readiness of resources in the field of digital forensics is still very lacking. The number of digital forensic certified auditors is very limited. Digital forensic software and tools require a relatively large allocation of costs. Previous research examined the dimensions of digital forensic support and moral development on fraud detection abilities. This study adds a task complexity dimension to fraud detection ability. This study aims to examine the effect of auditor competence, task complexity and digital forensic support on fraud detection capabilities. Sampling using the purposive sample method with BPK auditor respondents. The data analysis method used Structural Equation Modeling (SEM) and for path causality analysis using Path Analysis. The results of the study reveal that the auditor's competence variable and digital forensic digital support have a positive effect on the auditor's ability to detect fraud. While the complexity of the task does not affect the ability of the auditor to detect fraud.